(3CeGdj GdeMGedjs - (3GdeMGedj, GdVHj, CHh YHO Gddg, GdMSjf Hf ESeGYjd Hf eMeO Hf ESeGYjd, J (B330(3g`s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdMSjf YGUe Hf GdMSf (B... (3bGd MOKfG CHh YHO Gddg GdMSjf Hf ESeGYjd GdeMGedj (B... (3bGd MOKfG CHh GdCTYK CMeO(B...s
(3BNQgG (B:s
(3SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd(B: (3ef TgO Cf dG Edg EdG Gddg hCf eMeOG QShd Gddg MQeg Gddg Ydi GdfGQs
(3QhGjI CHj YeQ YHO GdhGMO Hf eMeO Hf YHO Gddg Hf egOj GdaGQSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B234s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs